Uterine adenomyolipoma. A case report and review of the literature - Basheska, Neli (Wiley-Blackwell, 2010)
Introduction. Uterine adenomyolipoma also termed adenolipoleiomyoma or lipoadenofibroma is a rare benign, polypoid or less frequently intramural lesion, considered to be of hamartomatous origin or represent an unusual type of benign Müllerian mixed tumour with a heterologous element. We report another case of this uncommon lesion and review the previously documented similar cases. Case Report. A polypoid endometrial mass measuring 28x8x5 mm was removed during explorative curettage from a 56-year old woman presented with postmenopausal vaginal bleeding. Histologically, it was composed of tubular and cystic glands within a background of connective tissue containing endometrial stroma, smooth muscle and mature adipose tissue. Many glands were of endometrial proliferative type, while elsewhere glands were of tubal type with cilia or occasionally of endocervical type. Neither the epithelial nor the mesenchymal elements showed any cytological atypia, necrosis or mitotic figures. Periglandular stromal condensation was also absent. The glandular epithelial cells were immunoreactive for cytokeratin, epithelial membrane antigen and vimentin, but negative for carcinoembryonic antigen. The endometrial stromal cells were CD10 positive; smooth muscle cells were desmin and alpha-smooth muscle actin positive, while adipocytes were S100 protein positive. The nuclei of most of the glandular cells and some of the endometrial stromal and smooth muscle cells were both ER and PR positive. The proliferation index (Ki-67) was less than 1%. Conclusion. After extensive literature search, the case presented in this article appears to be the ninth report of this unusual uterine lesion occurring most frequently in postmenopausal women and the seventh presenting as an endometrial polypoid mass.
Keywords: uterus; adenomyolipoma; histopathology; immunohistochemistry